Early weight loss predicts weight loss treatment response regardless of binge‐eating disorder status and pretreatment weight change. Issue 6 (10th April 2018) - Barnes, Rachel D.; Ivezaj, Valentina; Pittman, Brian P.; Grilo, Carlos M.
Abstract: Objective: Individuals seeking weight loss treatment have diverse pretreatment weight trajectories, and once enrolled, individuals' response to weight loss treatments also varies greatly and may be influenced by the presence of binge‐eating disorder (BED). Reported average weight losses may obscure these considerable differences. This study examined whether BED status and different weight‐related change variables are associated with successful weight loss treatment outcomes in a controlled treatment study. Method: Participants ( N = 89) with overweight/obesity, with and without BED, participated in a 3‐month weight loss trial in primary care with 3‐ and 12‐month follow‐ups. We tested the prognostic significance of four weight‐related change variables (the last supper, early weight loss, pretreatment weight trajectory, weight suppression) on outcomes (weight loss‐overall, weight loss‐"subsequent, " weight loss during second half of treatment). Results: Early weight loss was positively associated with weight loss‐overall at post‐treatment, and at 3‐month and 12‐month follow‐up. Early weight loss was positively associated with weight loss‐subsequent at post‐treatment only. No other weight‐related variables were significantly associated with weight loss. Models including BED status and treatment condition were not significant. Discussion: Participants with early weight loss were more likely to continue losing weight, regardless of BED status or treatment condition. The results highlight the importance of early dedication to weight loss treatment to increase the likelihood of positive outcomes.